KONTRIBUSI KOIN UMAYYAH TEMUAN SITUS BONGAL TERHADAP HISTORIOGRAFI ISLAM DI SUMATERA UTARA - Ning Arrumdani; Hasan Asari; Nabila Yasmin (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2022)
This paper discusses about the characteristics of Umayyad coins found at the Bongal Site and how the contribution of Umayyad coins to the historiography of the history of Islam in North Sumatra. The method of the research is of historical method by going through four stages. As part of methodology, numismatic and archeological approach are also applied in the research. The research found Bongal Site is an important archeological site that has been discovered since 2019. Various artifacts from the 7th to 11th centuries have been discovered at this site. In this study, there are 3 Umayyad coins that are the object of study. Umayyad coins found at the Bongal site have contributed to historiography in North Sumatra. The contribution is to become one of the supporting evidence for the theory of the entry of Islam into the archipelago, namely the Mecca theory, and Umayyad coin also contributes as a new interpretation space for the writing of Islamic history in North Sumatra and the archipelago that focuses on Numismatic studies.